Multimedia programming using Max/MSP and TouchDesigner : a step-by-step guide to designing, building, and refining immersive audio-visual applications and performance environments using Max and TouchDesigner /: a step-by-step guide to designing, building, and refining immersive audio-visual applications and performance environments using Max and TouchDesigner. (2014) - Lechner, Patrik
No abstract available